Asymmetric construction of acyclic quaternary stereocenters via direct enantioselective additions of α-alkynyl ketones to allenamides - Jiawen Wang (Nature Portfolio, 2021)
Acyclic quaternary stereocenters are widely present in a series of biologically active natural products and pharmaceuticals. Here the authors show an efficient chiral phosphoric acid catalyzed direct asymmetric addition of α-alkynyl acyclic ketones with allenamides to produce acyclic all-carbon quaternary stereocenters with excellent regioselectivities and high enantioselectivities: